A challenging case of arrhythmogenic right ventricular cardiomyopathy presenting as fulminant myocarditis. Issue 4 (28th April 2021) - Mahdavi, Mohammad; Hosseini, Leila; Mozzaffari, Kambiz; Zadehbagheri, Fatemeh; Rezaeian, Nahid
ABSTRACT: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is known as a primary genetic heart disease that leading to the myocardial deposition of fibrofatty tissue in right ventricular (RV) wall. Sometimes, it occurs in the left ventricular (LV) subepicardial wall. This study introduces a child referred to our hospital with influenza-like symptoms and ventricular tachyarrhythmia, followed by cardiac failure. However, in our subsequent evaluation, there was evidence of severe LV and RV dysfunction based on the echocardiography. Moreover, cardiac magnetic resonance showed not only the major criteria of ARVC but also those of Lake Luise seen in myocarditis. Regarding the deteriorating condition during the hospital course, he was later scheduled for heart transplantation. Finally, the histopathological study of explanted heart revealed RV myocyte atrophy with the infiltration of fibrofatty tissue in myocardium diagnostic of ARVC, resolving dilemma between ARVC and myocarditis.